Three-dimensional Electromagnetic Characteristics Analysis of Novel Linear Synchronous Motor under Lateral and Yaw Conditions of MAGLEV - Gang Lv; Zhixuan Zhang; Xiaodong Li (CES Transactions on Electrical Machines and Systems, 2022)
Dynamic stability analysis of superconducting electro-dynamic maglev train under lateral and yawing motion condition is the key research content. The novel three-dimensional electromagnetic model of integrated linear synchronous motor in electro-dynamic maglev train with yawing operation condition is proposed, which can not only simultaneously achieve the propulsion, levitation and guidance performances of maglev vehicle, but also analyze the dynamic stability performance of train with yawing condition. The three-dimensional analytical method is introduced for analyzing the electromagnetic force characteristics of the linear synchronous motor with the yawing operation condition. Firstly, the topology structure and operation principle of the linear synchronous motor with yawing attitude are proposed. Secondly, the three-dimensional analytical model and expressions of electromagnetic characteristics are obtained by equivalent circuit method and Fourier decomposition method, such as levitation force, guidance force, propulsion force and yawing torque, etc. Finally, the three-dimensional electromagnetic characteristics of the linear synchronous motor are calculated under yawing operation conditions of maglev train, and the correctness of the analytical theory is verified by the finite element analysis and measured data on the test line.